Effects of high-density lipoprotein targeting treatments on cardiovascular outcomes: A systematic review and meta-analysis. (29th August 2020) - Riaz, Haris; Khan, Safi U; Rahman, Hammad; Shah, Nishant P; Kaluski, Edo; Lincoff, A Michael; Nissen, Steven E
Abstract: Background: The effects of increasing high-density lipoprotein cholesterol on cardiovascular outcomes remain uncertain. Design: We conducted a meta-analysis to investigate the effects of high-density lipoprotein cholesterol modifiers (niacin, fibrates and cholesteryl ester transfer protein inhibitors) on cardiovascular outcomes. Methods: Thirty-one randomized controlled trials (154, 601 patients) with a follow-up of 6 months or more and a sample size of 100 or more patients were selected using MEDLINE, EMBASE and CENTRAL database (inception January 2018). Results: High-density lipoprotein cholesterol modifiers had no statistically significant effect on cardiovascular mortality in terms of relative risk (RR) (RR 0.94, 95% confidence interval (CI) 0.89–1.00, P = 0.05, I 2 = 13%) or absolute risk (risk difference −0.0001, 95% CI −0.0014, 0.0011, P = 0.84, I 2 = 28%). High-density lipoprotein cholesterol modifiers reduced the RR of myocardial infarction (RR 0.87, 95% CI 0.82–0.93, P < 0.001, I 2 = 37%). This significant effect was derived by the use of fibrates (RR 0.80, 95% CI 0.73–0.87, P < 0.001, I 2 = 22%) and meta-regression analysis showed that this benefit was consistent with an absolute reduction in low-density lipoprotein cholesterol. High-density lipoprotein cholesterol modifiers had no effect on stroke (RR 1.00, 95% CI 0.93–1.09, P = 0.94, I 2 = 25%) or all-cause mortality (RR 1.02, 95% CI 0.97–1.08, P = 0.48, I 2 = 49%). Meta-regression analyses failed to demonstrate a significant association of pharmacologically increased high-density lipoprotein cholesterol with key endpoints. In studies with background statin therapy, high-density lipoprotein cholesterol modifiers had no statistically significant impact on cardiovascular mortality, myocardial infarction, stroke or all-cause mortality ( P > 0.05). Conclusion: The use of high-density lipoprotein cholesterol modifying treatments had no significant effect on cardiovascular mortality, stroke or all-cause mortality. The beneficial effect on myocardial infarction was lost when drugs were used with statin therapy.